An exploration of the perceptions of community health workers on the enablers and barries to providing services in Nyanga district, Zimbabwe - Darikwa, Patricia (My University, 2016)
Background: The work of Community Health Workers is appreciated in most setups in both developing and developed countries. In Zimbabwe there are a number of cadres who are working to bridge the health services and the community. There has however been limited documentation on the perspectives of Community Health Workers on what enables them to do their work and also barriers they face in providing their services. Aim: The study aimed to explore the perceptions of CHWs on the enablers and barriers to providing services in Nyanga district in Zimbabwe. Method: The study used a qualitative methods of in-depth interviews with Community Health Workers and key informants and document reviews. A thematic content analysis was used to identify key themes. The themes were then further analysed to identify the enablers and barriers to community health work. Results and Conclusion: The major enablers of the CHW work were perceived to be the benefits which have accrued to the communities the CHWs were working with, the benefits which the CHWs had gained and the support given by the hospital, NGO and the community leadership. The following were perceived to be the major barriers to CHW work: limited access to health services by the communities from the health facilities driven by the weak macroeconomic conditions in the country, gaps in support services, workload and geographical coverage. The recommendations include improving the motivation of the CHWs through efficient payment system, improving on quality of care and processes in the service provision. The results provide insights into CHW work which can assist policy makers and managers in making informed decisions on the investments they make for the CHW programmes in Nyanga district and Zimbabwe in general.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Master of Public Health Johannesburg June 2016
Keywords: Community Health Workers; Health Services